Analisis Risiko Produksi Benih Kentang Bersertifikat Kelas Benih Dasar (G0) di PT Anugrah Agro Putra Kabupaten Bandung - Triloka Dewi Rahayu; Kustopo Budiraharjo; Migie Handayani (Universitas Galuh, 2026)
The production of certified potato seed, particularly Foundation Seed (G0), is a crucial stage in ensuring the sustainability of the potato seed system in Indonesia. High-quality seed availability strongly affects crop productivity and resilience. PT Anugrah Agro Putra, a certified potato seed producer in Bandung Regency, has substantial production capacity but faces various risks that may reduce seed quality and quantity. This study was conducted from October to December 2025 to analyze the level of G0 seed production risk, identify priority risk sources, and formulate effective mitigation strategies. A case study approach with purposive sampling was applied. Data were analyzed using the coefficient of variation (CV) to assess production fluctuations and the House of Risk (HOR) method phases 1 and 2 to identify risk agents and determine mitigation strategies. The results indicate that G0 seed production during 2023–2025 was fluctuative, with a CV value of 13.58%, indicating a high production risk. HOR phase 1 identified three priority risk agents: high intensity of pests and diseases, extreme climate and weather conditions, and labor negligence. HOR phase 2 generated mitigation strategies including proper pesticide application, regular labor training, routine crop monitoring, implementation of appropriate technology, development of standard operating procedures, improved production recording, enhanced sanitation, and periodic maintenance of facilities.